Drivers of Kausha Damu Practices in Tanzania: A Study of Socio-Economic, Institutional, and Cultural Factors Influencing Predatory Lending among Women Borrowers in Tanzania - Allen Emmanuel Mrindoko (Rescollacom (Research Collaborations Community), 2026)
The study investigated the factors influencing predatory lending in Tanzania highlighting the importance of institutional, socio-economic and cultural factors among women borrowers. Specifically, the study assessed the extent institutional, socio-economic and cultural factors have been contributing on predatory lending among women borrowers, and analysed the relationship between institutional, socio-economic and cultural factors; and predatory lending represented by excessively higher interest rate, high and hidden fees, aggressive sales tactics and higher default rate as signs of predatory lending. Descriptive research design following mixed method approach was employed in this study. The study was carried out in Dodoma Urban, Temeke and Morogoro Urban districts. The targeted population comprised of all women borrowers in these districts. The sampling frame consisted women who borrow from microfinance institutions, individual lenders and online lending platforms. The study applied both purposive and random sampling methods to select respondents and key informants (KIs). The purposive sampling technique was used to select three district community development officers as KIs, while random sampling technique was used to select 100 women borrowers from each districts, and thus make up of sample size of 300 respondents. Data were collected through self-administered questionnaire and in-depth interview; and analysed through descriptive statistics based on mean, standard deviation, range and correlations; and content analysis respectively. The findings revealed that the extent institutional, socio-economic and cultural factors influence predatory lending is very high. Also, the results show that institutional, socio-economic and cultural factors correlates with predatory lending. The results of binary logistic regression show those who reported that institutional, socio-economic and cultural factors are not favourable to them were likely to borrow from predatory lender. Based on the findings, this study concludes that women are multi-vulnerable across multiple factors: institutional, socio-economic and cultural; to predatory lending. Thus, the study calls for increased efforts to enforcement of stricter regulations on lending practices of microfinance and online lending platforms.